Application of blended learning in Islamic cultural history subjects to increase student learning interest - Zaimudin, Zaimudin; Pramudya, Muhamad Ihza (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The background to this research is because students have low interest in learning, so this research aims to explore how to apply the blended learning method which seeks to increase students' interest in learning. The method used in this research uses classroom action assessment with a qualitative approach, and data collection is carried out on students in class 8.4 MTs. Annajah Jakarta. The primary source in this research is data obtained from observation and reinforced with secondary sources in the form of references from books, journal articles and various other references. The results of this research are in the form of applications carried out using the PBL (Problem-Based Learning) blended learning method and convey that, there is an increase in student interest in studying Islamic cultural history subjects so that the stimulus provided can be conveyed well without catching up with the teaching material presented. so that it can make students feel burdened by the learning carried out that day.